Long‐term results of plaque excision combined with aggressive pharmacotherapy in high‐Risk patients with advanced peripheral artery disease (SAVE a LEG registry). Issue 3 (9th March 2013) - Kiesz, R. Stefan; Wiernek, Szymon L.; Wiernek, Barbara K.; Radvany, Martin G.; Buszman, Piotr P.; Szymanski, Radoslaw; Konkolewska, Magda D.; Martin, Jack L.; Buszman, Pawel E.
<x xml:space="preserve">Abstract</x> Background In United States alone there are more than 12 million people with peripheral artery disease (PAD). Long‐term outcomes of plaque excision in high‐risk population (patients with diabetes and patients with end stage renal disease on dialysis) are scarce. Methods Since November 2003, we treated 225 consecutive patients (138 male, mean age: 66.3 ± 12.4, range: 29–93) with SilverHawkTM plaque excision for critical limb ischemia or disabling claudication. A total of 367 procedures were performed treating 832 lesions (157 restenotic, 675 de novo). One hundred fifty‐five patients (68.9%) were diabetics, 74 (32.9%) were on dialysis. All patients were treated with statins, clopidogrel, aspirin, and aggressive glycemic control. The primary endpoint for our study was target lesion revascularization (TLR), and the secondary endpoint was an assessment of major adverse events (all cause death, amputation, TLR). Results The average time of observation was 2.2 ± 1.2 years. Procedural success rate was 99.4% with <30% residual stenosis achieved in 818 (98.9%) lesions. SilverHawk was used alone in 86.7%. No acute limb loss or major perforation occurred. Sixty (26.6%) patients had TLR. Long‐term mortality was 16.4%. Seven (3.1%) patients had to undergo major amputations and 7 (3.1%) minor amputations. Seventy (31.1%) patients had a major adverse event. Atorvastatin 80 mg was found to be independent predictor of survival, and major amputation was found to be independent predictor of mortality. Conclusions SilverHawk Plaque Excision combined with aggressive pharmacotherapy in this presented high‐risk population is associated with promising long‐term outcomes that compare favorably with accepted standards of care. © 2013 Wiley Periodicals, Inc.